A prática discursiva de Madonna: transgressão e conservadorismo na cena pop - Ziviani, Rodrigo (2017)
In our research for the master´s degree, we wanted to analyze the discursive practice of the pop female singer Madonna, according to the postulates of Dominique Maingueneau in Gênese dos Discursos (2005). According to the thesis of a global semantic, which regulates all the discursive plans, we intended to understand the regularities of the Madonna´s discursive practice. We analyzed representative fragments of her career, considering the materiality of different semioses, like the covers of the records, songs, music videos, concert videos and outfits, in periods classified for the specialized critics as her most or least groundbreaking ones. For this research, we selected material for each decade which the singer became a pop icon. From de 1980´s, we chose the albums True Blue and Like a Prayer. From the 1990´s, the chosen ones were Erotica and Ray of Light, besides the Sex book and the Blond Ambition Tour recording. From de 2000´s, we observed the album Confessions on a Dancefloor and the DVD of the Confessions Tour. And, from the recent decade, we opted for the MDNA and Rebel Heart albums, which live concerts were also integrated to this research. The corpus analysis allows to conclusion that the discursive practice of Madonna stays between the transgression and the conservatism, by means of two frequent themes in her work: sex and religion. This movement between transgress and conserve is possible by the exploitation of many sexuality expressions e trough the reincorporation of traditional values, like family and religiousness. The sexual and religiosity themes, according to our research, received ambiguous semantic treatment, which make possible relating other relevant themes, like feminism and patriarchate.